Concomitant recovery from left spatial neglect and inflammatory dysfunction of white-matter pathways in a case of acute disseminated encephalo-myelitis (ADEM). (October 2019) - Tomaiuolo, Francesco; Campana, Serena; Cecchetti, Luca; Galli, Rosita; Zucco, Gesualdo M.; Lasaponara, Stefano; Doricchi, Fabrizio
Abstract: Spatial neglect is an invalidating neuropsychological syndrome characterized by the inability of paying attention to the side of space contralateral to a unilateral brain damage. Recent studies have suggested that lesion of white-matter pathways plays an important role in producing spatial neglect by causing a widespread functional breakdown of the network of cortical and subcortical structures that regulates orienting of spatial attention. Nonetheless, this conclusion is largely based on the study of patients who suffer combined grey and white matter damage and should be better corroborated by the study of cases with selective or predominant white matter dysfunction. Here, we describe the clinical and MRI follow-up of a patient who suffered left spatial neglect due to inflammatory Acute Disseminated Encephalo-Myelitis (ADEM) that affected the white matter. Recovery from neglect was matched with recovery from inflammatory white-matter dysfunction, despite a concomitant and progressive increase in cortical atrophy and ventricular dilatation. These findings confirm the role of white matter lesion/dysfunction in the pathogenesis of left spatial neglect.